2019
DOI: 10.1039/c9ra01174a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and excellent electroresponsive properties of ideal PMMA@BaTiO3 composite particles

Abstract: A series of core–shell-structured poly(methylmethacrylate)@BaTiO3 (PMMA@BT) composite particles were constructed via the self-assembly of BT nanoparticles on the surfaces of PMMA cores through the covalent bonding of siloxane groups at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In this study, a water contact angle test was performed on commercially pure titanium (CpTi) and Ti13Nb13Zr alloy samples coated with a composite material made of 18% polycaprolactone (PCL) and variable concentrations of nano-barium titanate (9, 18, and 36% w/w). The surfaces of the PCL/BT composite particles were between hydrophobic (PCL) and super hydrophilic (BaTiO 3 ), 70 and the surface hydrophilicity steadily increased with BaTiO 3 concentration which agreed with the results of Liu et al in 2019, 71 and contradicts previous studies that reported water contact angles above 100 when different concentrations of nano-hydroxyapatite were mixed with PCL using different techniques and solvents. 72 However, this finding agrees with studies on zirconia implants that reported decreased water contact angle with increased ceramic material in the polymer coating.…”
Section: Resultssupporting
confidence: 82%
“…In this study, a water contact angle test was performed on commercially pure titanium (CpTi) and Ti13Nb13Zr alloy samples coated with a composite material made of 18% polycaprolactone (PCL) and variable concentrations of nano-barium titanate (9, 18, and 36% w/w). The surfaces of the PCL/BT composite particles were between hydrophobic (PCL) and super hydrophilic (BaTiO 3 ), 70 and the surface hydrophilicity steadily increased with BaTiO 3 concentration which agreed with the results of Liu et al in 2019, 71 and contradicts previous studies that reported water contact angles above 100 when different concentrations of nano-hydroxyapatite were mixed with PCL using different techniques and solvents. 72 However, this finding agrees with studies on zirconia implants that reported decreased water contact angle with increased ceramic material in the polymer coating.…”
Section: Resultssupporting
confidence: 82%
“…10 49,50 m-BT nanoparticles exhibited a similar crystal structure, while the intensity of characteristic diffraction peaks decreased slightly, which was due to the phosphate coupling agent. 51,52 The amorphous PMMA had a broad characteristic peak, and the maximum absorption peak was at 2y B 15.51. 53 PMMA-BT3 nanocomposites mainly showed the amorphous phase of the polymer, and the characteristic diffraction peaks of nanoparticles were suppressed by the coated polymer on the nanoparticles.…”
Section: Xps and Xrd Measurementsmentioning
confidence: 99%
“…The surface morphology of pristine MoS 2 displays nanoflakes with irregular shapes and sizes reported previously. The surface morphology of PMMA film (figure S3(a)) shows elongated particles with different shapes and sizes covering the substrate [49]. In contrast, the morphology of PVDF displays nearly spherical-shaped particles with different diameters (figure S3(b)).…”
Section: Morphological Analysis 331 Scanning Electron Microscopy (Sem...mentioning
confidence: 99%